Ta’lîm Maĥaratul Istima’ Li Mubtadîn Ghaira Nathiqina Bil lughatil Al- ‘Arabiyah - Haeria, Wa Ode; Kholiq Hasan, Moh. Abdul (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
يهدف هذا البحث إلى اكتشاف تعليم مهارة الاستماع لمبتدئين غير ناطقين بللغة العربية حيث إن هذه المهارة من أهم المهارت اللغوة التي يجب تطويرها لدى المتعلمين في مراحل تعلمهم المختلفة قبل تعليم مهارات اللغوية الأخرى الذي يتم اكتساب اللغة التامة من خلال إتقان هذه المهارة. ونوع البحث المستخدم في هذا البحث هو البحث الوصفي وقامت الباحثة بجمع البيانات وتحليلها ثم الاستنتاج. وأسفرت نتيجة البحث بتوضيح أن مهارة الاستماع إحدى المهارات في غاية الاهتمام بتعليمه والمعلم له دور كبير في هذا المجال لتوجيه المتعلم خلال دراسة مهارة الاستماع. وليست أهمية هذه مهارة يكتسبها الطفل في لغة الأم فقط بل كذلك بنسبة للمتعلمين الأجانب ودورها في دعم باقي المهارات اللغوية الأخرى مثل مهارة الكلام والقراءة والكتابة، ومراحل تعليمها بدءا من استقبال المعلومات وفهمها وتقييمها حتى الاستجابة،كما يتطرق إلى أنواع مهارة الاستماع وتقديم أساليب مختلفة لتعليمها التي تناسب المبتدئين في تعليم هذه المهارة و كذلك ذكر المعوقات التي تقع من خلال تعلم وتعليم مهارة الاستماع This research aims to explore the teaching of listening skill to non-native speakers of Arabic، as this skill is one of the most important language skills that must be developed in learners at different stages of their learning before teaching other language skills، which is acquired through mastery of this skill. The type of research used in this research is descriptive research and the researcher collected and analyzed the data and then drew conclusions. The result of the research resulted in clarifying that listening skill is one of the most important skills to teach and the teacher has a big role in this field to guide the learner during the study of listening skill. The importance of this skill is not only acquired by the child in the mother tongue، but also for foreign learners and its role in supporting other language skills such as speech، reading and writing، and the stages of teaching it starting from receiving، understanding and evaluating information to respond، as well as addressing the types of listening skill and providing different methods for teaching it that are suitable for beginners in teaching this skill as well as mentioning the obstacles that occur during the teaching of listening skill.